Eucalyptus torquata L. flowers: a comprehensive study reporting their metabolites profiling and anti-gouty arthritis potential - Ashour, Rehab; El-Shiekh, Riham A.; Sobeh, Mansour; Abdelfattah, Mohamed A. O.; Abdel-Aziz, Marwa M.; Okba, Mona M. (Scientific reports, 2023)
Gouty arthritis is one of the most common metabolic disorders affecting people. Plant based drugs can lower the risk of this health disorder. The anti-gouty potential of Eucalyptus torquata flowers methanol extract (ETME) was evaluated in vitro via measuring the inhibitory effects of five pro-inflammatory enzymes; xanthine oxidase (XO), hyaluronidase, lipoxygenase (5-LOX), cyclooxygenases COX-1, and COX-2, in addition to evaluating the inhibition of histamine release, albumin denaturation, membrane stabilization, tyrosinase, and protease inhibitory activities. Also, its antioxidant potential was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging assays and ferric reducing power assay (FRAP). HPLC-PDA-MS/MS was used to identify the metabolites in the tested extract. The latter exhibited substantial anti-arthritic properties in all assays with comparable potential to the corresponding reference drugs. HPLC-MS/MS analysis of this bioactive extract tentatively annotated 46 metabolites including phloroglucinols, gallic and ellagic acids derivatives, terpenes, flavonoids, fatty acids, and miscellaneous metabolites. Our study highlights the medicinal importance of E. torquata as an anti-gouty candidate and opens new avenues of gouty management.
Published: 31 October 2023
Gesehen am 24.09.2024